How can we turn the PI3K/AKT/mTOR pathway down? Insights into inhibition and treatment of cancer. Issue 6 (3rd June 2021) - Afify, Said M.; Oo, Aung Ko Ko; Hassan, Ghmkin; Seno, Akimasa; Seno, Masaharu
ABSTRACT: Introduction : The phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway is a fundamental regulator of cell proliferation and survival. Dysregulation in this pathway leads to the development of cancer. Accumulating evidence indicates that dysregulation in this pathway is involved in cancer initiation, progression, and recurrence. However, the pathway consists of various signal transducing factors related with cellular events, such as transformation, tumorigenesis, cancer progression, and drug resistance. Therefore, it is very important to determine the targets in this pathway for cancer therapy. Although many drugs inhibiting this signaling pathway are in clinical trials or have been approved for treating solid tumors and hematologic malignancies, further understanding of the signaling mechanism is required to achieve better therapeutic efficacy. Areas covered : In this review, we have describe the PI3K/AKT/mTOR pathway in detail, along with its critical role in cancer stem cells, for identifying potential therapeutic targets. We also summarize the recent developments in different types of signaling inhibitors. Expert opinion : Downregulation of the PI3K/AKT/mTOR pathway is very important for treating all types of cancers. Thus, further studies are required to establish novel prognostic factors to support the current progress in cancer treatment with emphasis on this pathway.